2014
DOI: 10.1590/s1806-37132014000100009
|View full text |Cite
|
Sign up to set email alerts
|

The burden of disease due to tuberculosis in the state of Santa Catarina, Brazil

Abstract: OBJECTIVE:To estimate the burden of disease due to tuberculosis in the state of Santa Catarina, Brazil, in 2009.METHODS:This was an epidemiological study with an ecological design. Data on tuberculosis incidence and mortality were collected from specific Brazilian National Ministry of Health databases. The burden of disease due to tuberculosis was based on the calculation of disability-adjusted life years (DALYs). The DALYs were estimated by adding the years of life lost (YLLs) and years lived with disability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 11 publications
4
16
0
2
Order By: Relevance
“…It was observed the predominance of males, in people in economically active age range, with less than eight years of education. These findings are in acordance with other studies carried out in other Brazilian scenarios 8 - 9 . Similarly, the study is consistent with the literature regarding the predominant clinical form of the disease, in which pulmonary TB was the most prevalent 2 , 7 - 8 .…”
Section: Discussionsupporting
confidence: 92%
“…It was observed the predominance of males, in people in economically active age range, with less than eight years of education. These findings are in acordance with other studies carried out in other Brazilian scenarios 8 - 9 . Similarly, the study is consistent with the literature regarding the predominant clinical form of the disease, in which pulmonary TB was the most prevalent 2 , 7 - 8 .…”
Section: Discussionsupporting
confidence: 92%
“…As it was expected, the burden of tuberculosis in Santa Catarina was higher among men than among women, which agrees with previously published epidemiological studies 7,10,20 . Mexico experienced a 56% incidence of tuberculosis among men in 1990-2010 20 , whereas in the Brazilian state of Minas Gerais, the rate was even higher (60.6%) 9 .…”
Section: Discussionsupporting
confidence: 92%
“…YLL, YLD, and DALY rates/100,000 inhabitants according to gender in Santa Catarina, Brazil, 2007. Rates 10 . The findings of our study are, for the most part, lower to those reported by other authors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It accounts for a quarter of preventable deaths in developing countries, with emphasis on adults generally and men aged 45-59 years old 1,2 . It is known as the "neglected calamity" not yet resolved in this century 3 .…”
Section: Introductionmentioning
confidence: 99%